Quercetin Attenuates Manganese-Induced Neurotoxicity in Mice Hippocampus by Regulation of Oxidative Stress and Tumour Necrosis factor Alpha Expression - Oloruntoba Adekeye, Adeshina; Adediran Fafure, Adedamola; First Ofogba, Oghenetega; Saka, Olusola; Anderson Enye, Linus; Oloruntoba Akintayo, Christopher; Olukayode Oni, James; Dayo Adedayo, Lawrence; Ojewale, Abdulfatai (International Journal of Human Anatomy, 2020)
The hippocampus is involved in learning and memory processes, an integral component of cognitive function. The aim of this study is to assess the efficacy of quercetin on manganese-induced neurotoxicity in the hippocampus of the adult mice. In this study, 40 adult mice of average weight of 18 –29g were randomly distributed into five groups of eight each. The brain was harvested and the region of the hippocampus was grossed for histological and immunohistochemical analysis. The results revealed a significant increased level of oxidative stress markers of manganese treated mice when compared with the normal control and quercetin treated animals (p<0.05). Immunohistochemical analysis also showed a decrease expression of Tumour necrosis factor alpha (TNFα) with quercetin treated animals when compared with manganese treated animals indicating its neuroprotective function. In addition, quercetin treated animals all had an improved working spatial memory in Y-maze test. The histological results also revealed a degeneration of pyramidal cells with a characteristic pyknotic activities at the granular layer of the hippocampus leading to neuronal integrity damage following chronic exposure to manganese but normal architectural design was however maintained with quercetin. Conclusively, exposure to manganese in excess may have adverse effect on extensive neuronal degeneration that could affect the learning, memory and possibly spatial navigation ability of miceand quercetin attenuates this induced neurotoxicity via inhibition of oxidative stress and reduction of TNF expression.
Keywords: Neurotoxicity; Manganese; Hippocampus; Cognition; Oxidative stress